Career Transformation and Entrepreneurship: Business Process Optimization through Internship at PT Sangkara Consulting Group - M. Gunawan; Fitri Widiastuti (Journal of Humanities, Community Service, and Empowerment, 2025)
This study aims to analyze the implementation of entrepreneurship internships at PT Sangkara Consulting Group and their impact on students' career development and entrepreneurship. This internship program not only provides students with the opportunity to gain practical experience in the business world but also helps them develop skills that are highly valued in entrepreneurship, such as problem-solving, risk management, and business strategy development. Although the direct impact on increasing the number of company customers has not been significant in the short term, this study shows that internships play a crucial role in enriching students' understanding of the business world and enhancing their entrepreneurial skills. This internship program also provides students with opportunities to expand their professional networks and make a positive contribution to their future career development. Through in-depth interviews with students and mentors at PT Sangkara Consulting Group, it was found that internships have a positive impact on the development of students' entrepreneurial skills. However, to maximize the impact of internships on the company's business performance, it is necessary to improve the quality of the program, including the development of internship content and strategies that are more focused on customer development and business process optimization. This internship program provides valuable experience that enables students to not only be ready to face the world of work but also develop the skills necessary to become competent entrepreneurs. Thus, the internship program at PT Sangkara Consulting Group has the potential to make a greater contribution to the development of entrepreneurship and business growth.